Towards exploratory talk in secondary-school CLIL: An empirical study of the cognitive discourse function ‘explore’ - Gerns, Pilar; Mortimore, Louisa (Language teaching research : LTR, 2025)
Exploratory talk is increasingly recognized in formal education for its role in enhancing students’ critical thinking and literacy skills, which are crucial for quality education both within and beyond school contexts. However, research shows that students often lack opportunities for inquiry-based learning and rarely receive explicit guidance on using language for reasoning, particularly in second language (L2) learning environments. Understanding how students engage in this complex function and effectively promoting it in L2 subject contexts remains a challenge. This study introduces an operational framework for the function of ‘explore’, based on L2 learning and socio-cultural theories and Dalton-Puffer’s construct of cognitive discourse functions (CDFs). It provides both quantitative and qualitative insights into how secondary-level content and language integrated learning (CLIL) students ( N = 113) from three different types of schools in Spain performed the ‘explore’ function orally, and it examines the role of epistemic modality in this meaning-making process by analysing the following features: (1) modal verbs, (2) modal adverbs and adjectives, (3) epistemic lexical verbs (ELVs), stance-taking forms, (4) discourse markers and the conditional ‘if’. A learner corpus was created for this analysis using Sketch Engine. The findings suggest that the CDF of ‘explore’ involves a combination of epistemic modality markers that serve as reasoning and exploratory discourse indicators. There is, however, a pressing need to raise teachers’ awareness of how language (through CDFs) supports students’ exploratory and deeper learning in L2 content-learning contexts. To this end, the discussion presents pedagogical implications for future research and practice in fostering exploratory reasoning, and where possible, embedding these skills in exploratory talk within CLIL classrooms.